2019
DOI: 10.1242/dev.170001
|View full text |Cite
|
Sign up to set email alerts
|

Doublesex controls specification and maintenance of the gonad stem cell niches in Drosophila

Abstract: Sex-specific development of the gonads is a key aspect of sexual dimorphism that is regulated by Doublesex/Mab3-related transcription factors (DMRTs) in diverse animal species. We find that in mutants for Drosophila dsx, important components of the male and female gonad stem cell niches (hubs and terminal filaments/cap cells, respectively) still form. Initially, gonads in all dsx mutants (both XX and XY) initiate the male program of development, but later half of these gonads switch to form female stem cell ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
1
22
1
Order By: Relevance
“…Conversely, if Fru expression is only a consequence of male-specific cell fate, changing Fru expression level would not alter the chances of a dsx mutant gonad developing a hub or TFs. As previously reported [ 21 ], dsx mutant gonads had a roughly equal chance of forming hubs or TFs (with another fraction forming no discernable niche structure, Fig 3C–3F ). When one copy of fru was removed in this genetic background ( dsx 1 /Df(3R)dsx 3 , fru Sat15 /+ ), we observed that the fraction of XY gonads with hubs decreased while the fraction that formed TFs increased ( Fig 3I ).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Conversely, if Fru expression is only a consequence of male-specific cell fate, changing Fru expression level would not alter the chances of a dsx mutant gonad developing a hub or TFs. As previously reported [ 21 ], dsx mutant gonads had a roughly equal chance of forming hubs or TFs (with another fraction forming no discernable niche structure, Fig 3C–3F ). When one copy of fru was removed in this genetic background ( dsx 1 /Df(3R)dsx 3 , fru Sat15 /+ ), we observed that the fraction of XY gonads with hubs decreased while the fraction that formed TFs increased ( Fig 3I ).…”
Section: Resultssupporting
confidence: 85%
“…In dsx mutants, half of both XX and XY gonads remain as hubs, while the other half switch to form TFs during the L3 stage. As a result, either a hub or TFs can be found in both XX and XY gonads [ 21 ]. We examined Fru expression levels in late L3 dsx null gonads and categorized the results by chromosomal sex and niche fate (hub vs. TFs, Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations